"Settling Some Very Important Principles of Colonial Law": Three "Forgotten" Cases of the 1840's - Hickford, Mark (Victoria University of Wellington Law Review, 2004)
This article reintroduces the "forgotten" cases of R v Taylor, Attorney-General v Whitaker and Scott v Grace and considers their specific historical contexts. They raise controversial questions about the extent of the New Zealand governor's ability to grant lands outside of the provisions of local ordinances and imperial statutes by using the prerogative. The article notes the flow-on effects of the policy lacuna created by these judgments. The judgments of Justice Chapman and Chief Justice Martin caused considerable unease on the part of the colonial government and policy-makers in London as well as some New Zealand Company operatives. This in turn led to the subsequent legislative and policy efforts to qualify the reach of prerogative powers in colonies. The text of the cases is appended to this article.